Radiogenic isotope data (Nd and Pb) of IODP Site 303-U1307 - Isabela Moreno Cordeiro Sousa; Claude Hillaire-Marcel; Anne de Vernal; Jean-Carlos Montero-Serrano; Aurélie Marcelle Renée Aubry (PANGAEA, 2024)
This dataset consists of analyses of a Pliocene interval at Integrated Ocean Drilling Program (IODP) site 303-U1307. The site is located on Eirik Drift and was cored in 2004. The radiogenic isotope data (Nd and Pb) consist of 53 samples and were measured using a Nu Plasma II Multi-Collector Inductively Coupled Plasma Mass Spectrometer (MC-ICP-MS). The radiogenic isotope data (Nd and Pb) were used to infer changes in sediment provenance across the mPWP. All data were generated in 2023. The timespan of the data set is from ~2.9 Ma to 3.2 Ma (~300 ka total duration), which covers the mid-Pliocene Warm Period (mPWP; 3.025-3.264 Ma) with an average sampling resolution of ~4 ka.